PENGARUH GHRM, TASK-RELATED PRO-ENVIRONMENTAL BEHAVIOR, PROACTIVE PRO-ENVIRONMENTAL BEHAVIOR, GREEN INNOVATION PRACTICES TERHADAP ENVIRONMENTAL PERFORMANCE - Nurulfadhilah, Laely; Emilisa, Netania (E-Jurnal Manajemen, 2023)
Penelitian ini memiliki tujuan yaitu untuk menganalisis pengaruh positif Green Human Resources Management, Task-Related Pro-Environmental Behavior, Proactive Pro-Environmental Behavior, Green Innovation Practices terhadap Environmental Performance di rumah sakit provinsi Banten dengan menggunakan statistik deskriptif dan regresi linear berganda. Pengumpulan data yang dilakukan dalam penelitian ini menggunakan studi kepustakaan serta kuesioner yang disebarkan secara online melalui media google form dan diukur dengan skala likert. Sampel sebanyak 160 orang ditentukan dengan menggunakan purposive sampling. Penelitian ini menunjukkan GHRM, Task-Related Pro-Environmental Behavior, Proactive Pro-Environmental Behavior, GIP berpengaruh positif terhadap Environmental Performance. Implikasi manajerial dalam peneltian ini perlu memperhatikan beberapa variabel agar penerapannya dapat berjalan efektif dan meningkatkan environmental performance. Serta keterbatasan yang dimiliki yaitu penelitian ini hanya dilakukan di rumah sakit daerah Banten dan saran lebih lanjut dalam temuan ini telah dibahas untuk memantau praktik GHRM, ProEnvironmental Behavior, dan GIP yang mempengaruhi Environmental Performance karyawan.   This study has the objective of analyzing the positive influence of Green Human Resources Management, Task-Related Pro-Environmental Behavior, Proactive ProEnvironmental Behavior, Green Innovation Practices on Environmental Performance in Banten provincial hospitals using descriptive statistics and multiple linear regression. The data collection carried out in this study used a literature study and a questionnaire which was distributed online through the Google form media and was measured by a Likert scale. A sample of 160 people was determined using purposive sampling. This study shows that GHRM, Task-Related Pro-Environmental Behavior, Proactive Pro-Environmental Behavior, GIP have a positive effect on Environmental Performance. Managerial implications in this research need to pay attention to several variables so that the application can run effectively and improve environmental performance. As well as the limitations, namely this research was only conducted in a Banten regional hospital and further suggestions in this finding have been discussed to monitor GHRM, Pro-Environmental Behavior, and GIP practices that affect employee Environmental Performance.